ANALISISASAS PERADILAN CEPAT SEDERHANA DAN BIAYA RINGAN DIKAITKAN DENGANDUE PROCESS OF LAWTERHADAPGUGURNYA PRAPERADILAN BERDASARKAN PASAL 82 AYAT (1) HURUF D KITAB UNDANG-UNDANG HUKUM ACARA PIDANA JO PUTUSANMAHKAMAH KONSTITUSI NOMOR 102/PUU-XIII/2015 - Angga Hijrahtul Mufit; Zulfikar Jayakusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The principle of due process of law in criminal procedure law contains two things processesand procedures. There must be no legal process without procedures, and the procedure is carriedout without the process of this procedure is prohibited in the procedural law. Based on LawNumber 8 of 1981 concerning Criminal Procedure Law, hereinafter referred to as KUHAP. Thescope of pretrial authority is regulated in Article 1 number 10 Jo Article 77 KUHAP Pre-trial aimsto protect the rights of suspects in the level of investigation and prosecution. Pretrial isstrengthened by the Constitutional Court Decision Number 21 / PUU-XII / 2014. Addition ofpretrial authority to examine and adjudicate whether or not the determination of the suspect, thevalidity of the search and acts of seizure. Through the Constitutional Court Decision Number Case102 / PUU-XIII / 2015 states Article 82 Paragraph (1) letter d of the Criminal Procedure Code iscontrary to the 1945 Constitution and does not have binding legal force as long as the phrase "acase has begun to be examined" is not interpreted the case has been delegated and the first trial hasbeen submitted to the subject matter on behalf of the pretrial defendant/ applicant".The purpose of this essay is: First, to know the principle of fast, simple and low-cost justiceassociated with due process of law against the death of pretrial based on Article 82 Paragraph (1)Letter d of the Criminal Procedure Code jo Decision of the Constitutional Court number 102 /PUU-XIII / 2015. Second, to find out article 82 paragraph (1) letter d of the Criminal ProcedureCode jo Decision of the Constitutional Court number 102 / PUU-XIII / 2015 has used due processof law.This type of research is normative legal research. Namely reviewing the principle of law.From the results of the problem research there are two main things that are concluded, first, thatthe word segara contained in Article 50 paragraph (2), (3) and Article 143 paragraph (1) of theKUHAP has been interpreted carelessly without looking at the quality of a case file which will bedelegated to the court and does not consider the principle of proof of the second, that there is nolegal standing against the pretrial death verdict carried out by investigators and / or prosecutors inthe delegation of court case files. Even though the pretrial decision is declarative in nature, it stateswhether the actions taken by investigators and / or prosecutors are valid or not and have fulfilledlegal processes and procedures fairly as contained in the principle of due process of law.Keywords: The Principle of Simple Fast Justice and Low Cost - Due Process of Law - Death ofPretrial